KALENDER AUF DEUTSCH SEBAGAI MEDIA BELAJAR MANDIRI DALAM MENINGKATKAN KETERAMPILAN MENULIS BAHASA JERMAN - Rahmadan, Rizqi Dwi; Wahyuningsih, Fahmi (LATERNE, 2023)
Writing skill is a core competence that concentrates on students' ability to compose and produce simple written texts iniorder to beiable to convey information according toithe topic being studied by paying attention to the linguistic elements contained in the text according to the context of its use. One of the factors that causes difficulties in writing skills is the lack of use of student vocabulary. From the results of observations on PLP at SMAN 1 Surabaya, the field findings showed that class X students were still lacking in skills in writing words or sentences in German, especially in date material (Datum) due to a lack of regular and continuous use of vocabulary and implementing it in daily activities. day. Therefore the auf Deutsch Calendar was created as a learning medium that students can use independently to increase the vocabulary for writing date (Datum) skills contained in class X Semester 1 material. The formulationiiof the problemiiin this researchiiis howiito developiithe auf Deutsch Calendar as an independent learning medium in improve German writing skills in class X students?. The aimiiof the researchiwas to developiand find out the feasibility of the Auf Deutsch Calendar media in improving German writing skills in class X students. The method used was the development of the ADDIE model and carried out until the Development stage. While data collection comes from validation sheets byiimaterialiiexperts. and mediaiexperts. iFrom theiiresults of the media validation sheet, a percentage of 94% was obtained, while the material validation sheet obtained a percentage of 85%, which means that it is in a very good category and is suitable for use.